A REVIEW ON INDIAN TRIBAL PLANTS AND THEIR BIOGENIC PROPERTIES - K, Anju; L, Anitha Jegadeeshwari; D, Vidhya Lakshmi; N, Nagendra Gandhi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Green synthesis of silver nanoparticles (AgNPs) is considered to be nature-friendly and risk-free to the ecosystem. India is copious in biodiversity; the traditional medicine consists of the plant as a major component. The tribal people who lived in the rural region are entirely dependent on the tribal plant for their medical emergencies. These tribal plants have attracted the modern drug industry to develop drugs which are economical with minimal side-effects. The present study focuses on the tribal plants such as Aegle marmelos, Andrographis paniculata, Acacia arabica, Ficus religiosa, Cassia auriculata, Punica granatum, and Tinospora cordifolia used by the Bhilla, Irular, Dimasa, Paliyan Sholaga, and Dantewada tribes of India for their antimicrobial activity. Since these tribal plants are well known for its medicinal properties, the AgNPs synthesized from these plants were found to have enhanced antimicrobial activity than the pure plant extract.